2018
DOI: 10.3390/su10061834
|View full text |Cite
|
Sign up to set email alerts
|

Research on Financial Pressure, Poverty Governance, and Environmental Pollution in China

Abstract: The traditional environmental governance theory attributes pollution to the result of market failure, but ignores the institution-level factors and the possibility of government failure. Using provincial panel data from 2001 to 2016 in China, and by drawing impulse response function graphs and building PVAR models, this paper studies the financial pressure and poor governance effect on environmental pollution. Financial pressure represents fiscal decentralization and debt pressure. The study finds that the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 56 publications
0
12
1
Order By: Relevance
“…Regarding the different amount of investments every business unit puts into equipment updates and the application of new technologies, and taking into account the fact that they may be used to solve specific environmental problems [109,110], the last investments were assessed by taking into account the field of environmental activities. It should be noted, as well, that the importance of investments, and their impact on poverty rates, may be assessed by taking into account the pollution rate changes that are affected by investments [111]; therefore, the research is conducted including air, water, etc., pollution rates caused by the business units operating in the production sector.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the different amount of investments every business unit puts into equipment updates and the application of new technologies, and taking into account the fact that they may be used to solve specific environmental problems [109,110], the last investments were assessed by taking into account the field of environmental activities. It should be noted, as well, that the importance of investments, and their impact on poverty rates, may be assessed by taking into account the pollution rate changes that are affected by investments [111]; therefore, the research is conducted including air, water, etc., pollution rates caused by the business units operating in the production sector.…”
Section: Methodsmentioning
confidence: 99%
“…Zhang and Zhao [9] suggested that decentralization might help the control of environmental pollution. First, the level of environmental pollution varies significantly across different regions of a country, and it is difficult for a central government to provide environmental public goods for regions of different environmental conditions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides, the PVAR is estimated by a GMM estimation (Abrigo & Love, 2016;Liu & Kim, 2018). To analyze a PVAR model, IRF and variance decomposition function (VD) are applied due to their wide acceptance (Galariotis et al, 2018;Z. Zhang & Zhao, 2018).…”
Section: Model Settingmentioning
confidence: 99%